The Electrical Detection of Lead Ions Using Gold‐Nanoparticle‐ and DNAzyme‐Functionalized Graphene Device. Issue 2 (11th September 2012) - Wen, Yanqin; Li, Fabien Yi; Dong, Xiaochen; Zhang, Jun; Xiong, Qihua; Chen, Peng
<x xml:space="preserve">Abstract</x> An electronic Pb2+ sensor, with high sensitivity and specificity, was developed based on DNAzyme‐ and gold‐nanoparticle‐functionalized graphene transistor. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>